Low-dose captopril in the treatment of severe refractory hypertension associated with renal failure. Issue 681 (July 1982) - Bell, G. M.; Doig, A.; Watson, M. L.; Muir, A. L.; Winney, R. J.
Abstract : Six patients with severe refractory hypertension and chronic renal failure were treated with a low dose of captopril (mean daily dose 75 mg) in combination with dietary sodium restriction, frusemide and either metoprolol, labetalol or prazosin. Sustained control of blood pressure was achieved in all six patients. Adverse effects noted were severe hyperkalaemia (2 patients), skin rashes (2 patients) and taste disturbance (1 patient).